2015
DOI: 10.1038/bmt.2014.325
|View full text |Cite
|
Sign up to set email alerts
|

Secondary malignancies following high dose therapy and autologous hematopoietic cell transplantation-systematic review and meta-analysis

Abstract: We performed a systematic review and meta-analysis of randomized controlled trials comparing autologous hematopoietic cell transplantation (HCT) with other treatment modalities to analyze the risk for various secondary malignancies (SMs). Relative risks (RR) with 95% confidence intervals were estimated and pooled. Our search yielded 36 trials. The median follow-up was 55 (range 12-144) months. Overall, the RR for developing SMs was 1.23 ((0.97-1.55), I 2 = 4%, 9870 patients). Subgroup analysis of trials assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
(39 reference statements)
1
10
0
1
Order By: Relevance
“…31,32 Although scleroderma is associated with an increased risk of cancer, chemotherapy and irradiation are also associated with increased cancer risk. 33,34 Patients who are exposed to total-body irradiation are at increased risk for secondary cancers over a lifetime. Additional follow-up will be needed to quantify the risk of late cancer in patients with scleroderma who are treated with total-body irradiation as well as long-term outcomes of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Although scleroderma is associated with an increased risk of cancer, chemotherapy and irradiation are also associated with increased cancer risk. 33,34 Patients who are exposed to total-body irradiation are at increased risk for secondary cancers over a lifetime. Additional follow-up will be needed to quantify the risk of late cancer in patients with scleroderma who are treated with total-body irradiation as well as long-term outcomes of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…activity in these heavily pretreated patients 62,67,85,90 ; therefore, the use of these therapies earlier in the treatment course of lymphoma might increase the likelihood of success, if for no other reason than patients are more likely to be healthy enough to undergo such treatment, and because the disease is likely to still be sensitive to chemotherapy, thus enabling lower lymphoma burdens to be obtained before cell infusion. Application of CAR-T-cell therapy earlier in the course of treatment might also avoid some of the negative consequences of prolonged exposure to cytotoxic agents, such as the development of myelodysplastic syndrome and other secondary malignancies, which are a substantial risk, especially following auto-HSCT 157,158 . Another potential advantage is that patients who have never been exposed to chemotherapy might have higher blood T-cell counts and perhaps T cells that are more appropriate for CAR-T-cell therapy -both of these factors would facilitate production of CAR T cells.…”
Section: Improving Car-t-cell Therapymentioning
confidence: 99%
“…In childhood cancer studies, there are multiple reports on effect of radiation and/or chemotherapy on risk of subsequent secondary malignant solid tumors. [34][35][36][37] Irradiation containing conditioning regimens have been identified as a risk factor for posttransplant malignancy in patients with severe aplastic anemia and FA 20,38 ; and similar efforts of removing radiation from the conditioning regimen have been successful in patients with severe 39 aplastic anemia. A study by Rosenberg et al showed a trend toward increasing malignancy in patients with FA receiving a TBI-based regimen.…”
Section: Discussionmentioning
confidence: 99%